Influence of the storage environment on the physiological quality of millet seeds (Pennisetum glaucum (L.) R. Br.) - Silva, Girlanio Holanda da [UNESP]; Toledo, Mariana Zampar; Teixeira, Renake Nogueira; Rossi, Rubiana Falopa; Nakagawa, Joao [UNESP] (Abrates-assoc Brasileira Technologia Sementes, 2019)
Millet is a species of the grass family used in cattle pastures, for hay, for silage, and in soil cover in notillage systems. However, studies on seed production and post-harvest techniques for this species have not been sufficiently developed, considering the demand for and potential of this crop. The objective of this study was to monitor the physiological quality of millet seeds stored in porous packaging. Millet seeds were stored under four ambient conditions (natural laboratory environment, dry chamber, refrigerator, and freezer). Physiological quality was evaluated by germination and vigor tests before and during storage each year, up to six years for the dry chamber and natural laboratory environment, and up to 12 years for the refrigerator and freezer. Analysis of variance was conducted on the data, which were in 4 x 6 and 2 x 12 (environment and storage period) factorial arrangements. The means of the environments were compared by the Tukey test (p <= 0.05) and the storage periods by regression analysis. The germination capacity of millet seeds is best conserved in a refrigerator and freezer, and they remain viable for up to twelve years of storage under these conditions.
Keywords: germination; conservation; physiological quality